Nilai Kesetaraan Lahan dan Hasil Jagung Manis Tumpangsari Dengan Kacang-Kacangan di Pertanian Organik - Leonardo Dharmawangsa; U. Nujanah; H. Pujiwati; N. Setyowati; Prasetyo Prasetyo (xxxx-xxxx, 2020)
Dharmawangsa L, NujanahU, Pujiwati H, Setyowati N, Prasetyo P. 2020. Equity value of land and sweet corn poducts intercropping planting patterns with nuts in organic farming. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Intercropping is one of the solutions to increase crops with an organic system. This study aims at determining the highest productivity of intercropping sweet corns with beans planted at different times and determining the efficiency of land use when planting beans in the intercropping system. This research was carried out in August - November 2019, in the UNIB Closed Agro Ecosystem Field Laboratory, Air Duku Village, Selupu Rejang District, Rejang Lebong Regency, at an altitude of +1054 m asl, and has been a pesticide-free land for the last 10 years. This study employed a non-factorial completely randomized block design (RAKL) with three replications. The treatment applied was the intercropping system of sweet corns with peanuts, soybeans, and/or long beans planted at 15, 10, 5, and 0 days before planting sweet corns. Variable data were collected and analyzed using analysis of variance (ANOVA) level of 5%. The results showed that the highest productivity was obtained in the intercropping treatment of sweet corn and long beans planted 5 days before planting sweet corn with NKL 1.64. The intercropping system of sweet corns with peanuts, soybeans, and/or long beans with various planting times is more efficient in land use if compared to monocultures with NKL> 1.